Vertical Charge Transport via Small Polaron Hopping within TIPS‐Pentacene Lamellar Single Crystal. Issue 25 (16th May 2017) - Wang, Jiawei; Liu, Tianjun; Dong, Ji; Li, Molin; He, Jun; Jiang, Chao
Abstract : A modified liquid method is employed to grow an ultralarge 6, 13‐bis(triisopropylsilylethynyl)pentacene crystal, ensuring fabrication and measurements of the two terminal devices. The hole transport mechanism is studied by analyzing the space charge limited currents (SCLCs) at various temperatures. Modified SCLC theory with a small polaron hopping model is developed and employed to successfully simulate the I – V curves. Values of effective hopping distance, transfer integral, and reorganization energy are extracted and reasonably discussed. A scenario is suggested that hopping transport takes place from one molecule to its nearest neighbor along the c‐ axis, with every molecule acting as a trapping center. Abstract : Sandwich‐like two terminal devices based on ultra‐large 6, 13‐bis(triisopropylsilylethynyl)pentacene (TIPS‐pentacene) single crystals are electrical characterized with temperature dependence measurements. A space charge limited current (SCLC) model based on small polaron hopping is developed to simulate the current‐voltage characteristics, outcomes of which present a scenario that multiple hopping transport takes place with holes transferring from one molecule to its nearest neighbor along the crystal's c‐axis.